LOCAL BENGKULU LANGUAGE INTERFERENCE ON SPEAKING SKILLS IN ARABIC LANGUAGE LEARNING AT MAN ISLAM CENDEKIA BENGKULU - Falahun Ni'am; Hidayaturrahman, M; Khosi'in, Khosi'in; Hidayat, Nur; Klaina, Mekki (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2025)
This study explores the impact of Bengkulu local language interference on the speaking skills of students learning Arabic at MAN Islam Cendekia Bengkulu. While language interference in second language acquisition is well-documented, there is limited research on the influence of regional languages, such as Bengkulu, in the Southeast Asian educational context. Using a qualitative approach, this study involved interviews and classroom observations of 30 students to identify patterns of Interference in Arabic pronunciation, sentence structure, and vocabulary. The findings revealed significant phonetic similarities between Bengkulu and Arabic, with local language phonetics contributing to noticeable speech errors, particularly in consonant articulation and sentence construction. These errors were linked to specific characteristics of the Bengkulu language, which affect the student's ability to produce Arabic sounds and structures accurately. The study emphasizes the need for targeted strategies to address language interference in Arabic language teaching. It recommends adjustments in curriculum design and teaching methods to help mitigate the impact of local language interference, ultimately improving students' Arabic proficiency. The implications of this research extend to teacher training and materials development, urging educators to incorporate contrastive linguistic analysis and oral drills that directly target problematic phonetic and syntactic areas. Future studies are encouraged to examine interference effects across other local Indonesian languages and explore longitudinal changes in student performance following targeted instructional interventions.